In situ growth of g-C3N4 on clay minerals of kaolinite, sepiolite, and talc for enhanced solar photocatalytic energy conversion - Chen, Yunhui; Wen, Liping; Chen, Jinxin; Luo, He'an; Liu, Jikai (Applied clay science, 2022)
The clay mineral/g-C3N4 composites were prepared through a simple one-pot synthesis with acid-treated clay minerals and melamine as precursors. Three typical clay minerals, e.g., kaolinite, sepiolite, and talc, were adopted as photocatalyst carriers. Notably, the acid-treated clay minerals coupled with g-C3N4 in three different ways. The kaolinite/g-C3N4 composite, in particular, proceeded with an intercalation reaction due to the in situ growth of g-C3N4 within the layers of acid-treated kaolinite, leading to the expansion of kaolinite layers and a prominently large specific surface area of 61.9 m2 g−1. The resultant composites were used in photocatalytic H2 generation by water splitting and CO2 reduction, exhibiting superior photocatalytic performance to the g-C3N4. Among the obtained composites, the optimized kaolinite/g-C3N4 showed the best photocatalytic activities, e.g. 3.03 μmol g−1 h−1 of CO evolution and 385 μmol g−1 h−1 of H2 evolution, compared with merely 0.91 μmol g−1 h−1 of CO evolution and 96.4 μmol g−1 h−1 of H2 evolution for bare g-C3N4. The superior performance of kaolinite/g-C3N4 can be ascribed to the large specific surface area and better distribution of g-C3N4, which can enhance the light absorption, increase the number of active sites and favor the charge separation. [Display omitted] •The g-C3N4 was in situ grown on three types of acid-treated clay minerals.•The clay minerals coupled with the g-C3N4 in three distinctive manners.•The composites all exhibited higher photocatalytic activities than the g-C3N4.•The kaolinite/g-C3N4 composite showed the best photocatalytic performance.